1981
DOI: 10.1080/03014468100005111
|View full text |Cite
|
Sign up to set email alerts
|

Menarche in Newcastle upon Tyne girls

Abstract: Age at menarche was recorded for 699 white Newcastle upon Tyne girls taking part in a longitudinal study of growth and development during puberty. Girls from large (5+) families started menstruation about five months later than girls from small families. This effect was observed only among girls with fathers in manual occupations. The occurrence of menarche had a peak in January and a possible secondary peak about August. Height and to some extent weight increased with the age at menarche, while arm circumfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 4 publications
3
15
0
Order By: Relevance
“…Our results are consistent and showed the same pattern that many authors found in several populations, such as France (Demoulin, 1998), England (Roberts et al, 1971;Billewicz et al, 1981;Dann and Roberts, 1993;Roberts, 1994), South Africa (Cameron and Nadgdee, 1996), Poland (Laska-Mierezejewska, 1995), and Spain (Sánchez-Andrés, 1997Apraiz, 1999) ( Tables 7, 8). The range that we found in our sample is similar to those found in the above populations.…”
Section: Family Size and Birth Ordersupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent and showed the same pattern that many authors found in several populations, such as France (Demoulin, 1998), England (Roberts et al, 1971;Billewicz et al, 1981;Dann and Roberts, 1993;Roberts, 1994), South Africa (Cameron and Nadgdee, 1996), Poland (Laska-Mierezejewska, 1995), and Spain (Sánchez-Andrés, 1997Apraiz, 1999) ( Tables 7, 8). The range that we found in our sample is similar to those found in the above populations.…”
Section: Family Size and Birth Ordersupporting
confidence: 92%
“…This was found in studies in Poland (Bielicki et al, 1986;Laska-Mierezejewska, 1995), in Hungary (Bodzsar, 1975), in Khartoum (Sudan) (Attallah et al, 1983), in Nigeria (Oduntan et al, 1976;Uche and Okorafor, 1979), in Egypt (Attallah, 1978), and South Africa (Henneberg and Louw, 1995). Family size and birth order also have shown a significant effect on age at menarche, with girls in large families exhibiting a delay of maturation (Roberts et al, 1971;Billewicz et al, 1981;Roberts, 1984, 1993;Clegg, 1980;Cameron and Nadgdee, 1996;Sánchez-Andrés, 1997;Apraiz, 1999). Other factors such as nutrition (Simodon et al, 1997), seasonality (Boldsen, 1992), physical activity (Malina, 1983), and altitude level (Gonzales et al, 1996) also have shown significant effects on age at menarche.…”
mentioning
confidence: 71%
“…Studies of girls in Newcastle-upon-Tyne, Northumberland and South Shields found median ages at menarche of 13·3, 13·3 and 13·4 years respectively (Billewicz et al, 1981;Roberts et al, 1971Roberts et al, , 1975. These small differences in median menarcheal ages may be due to systematic error in recall in the Thousand Families data, random variation or cohort effects for different birth years.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Previous papers from the present study in Newcastle upon Tyne dealt with menarche, early patterns of menstruation, sexual maturation in boys and girls Thomson 1980, 1981 a, b) and with the prevalence ofacne in relation to pubertal status (Fellowes, Billewicz and Thomson 1981). In this communication, a summary of the anthropometric findings is provided and some biological and social correlates of adolescent growth are considered.…”
Section: Introductionmentioning
confidence: 93%